Inert gas washout: background and application in various lung diseases (Swiss Medical Weekly, 2017)
Multiple breath inert gas washout (MBW) is a lung function technique to measure ventilation inhomogeneity. The technique was developed more than 60 years ago, but not much used for many decades. Technical improvements, easy protocols and higher sensitivity compared with standard lung function tests in some disease groups have led to a recent renaissance of MBW. The lung clearance index (LCI) is a common measure derived from MBW tests, and offers information on lung pathology complementary to that from conventional lung function tests such as spirometry. The LCI measures the overall degree of pulmonary ventilation inhomogeneity. There are other MBW-derived parameters, which describe more regional airway ventilation and enable specific information on conductive or acinar ventilation inhomogeneity. How this specific ventilation distribution is exactly related to different disease processes has not entirely been examined yet. MBW measurements are performed during tidal breathing, making this technique attractive for children, even young children and infants. These benefits and the additional physiological information on ventilation inhomogeneity early in the course of lung diseases have led to increasing research activities and clinical application of MBW, especially in paediatric lung diseases such as cystic fibrosis (CF). In these patients, LCI detects early airway damage and enables monitoring of disease progression and treatment response. Guidelines for the standardisation of the MBW technique were recently published. These guidelines will, hopefully, increase comparability of LCI data obtained in different centres or intervention trials in children and adults. In this non-systematic review article, we provide an overview of recent developments in MBW, with a special focus on children. We first explain the physiological and technical background to this technique with a short explanation of several methodological aspects that are important for understanding the principle behind the technique and enable high quality measurements. We then provide examples of MBW application in different lung diseases of children and adults, with regards to both clinical application and research activities. Lastly, we report on ongoing clinical trials using MBW as outcome and give an outlook on possible future developments.